Evidence-based medicine best practice or restrictive dogma - Sheridan, Desmond J. (Desmond John) (Imperial College Press, 2016)
The concept of evidence-based medicine was launched in 1991 as a new paradigm to inform medical practice and has risen to be regarded as the gold standard. It rapidly gained the attention of medics, health service managers and the general media as it presented a means to improve efficiency and effectiveness of service delivery